Co‐design development of a decision guide on eating and drinking for people with severe dementia during acute hospital admissions - Kanthee Anantapong; Andrea Bruun; Anne Walford; Christina H. Smith; Jill Manthorpe; Elizabeth L. Sampson; Nathan Davies (Wiley, 2023)
Abstract Introduction Using co‐design processes, we aimed to develop an evidence‐based decision guide for family carers and hospital professionals to support decision‐making about eating and drinking for hospital patients with severe dementia. Methods Following a systematic review, we interviewed people with mild dementia, family carers and hospital professionals in England. We then held co‐design workshops with family carers and hospital professionals. In parallel with the workshops, we used a matrix to synthesize data from all studies and to develop a decision guide prototype. The prototype was iteratively refined through further co‐design workshops and discussions among researchers and Patient and Public Involvement (PPI) representatives. We conducted user testing for final feedback and to finalize the decision guide. Results Most participants acknowledged the limited benefits of tube feeding and would not use or want it for someone with severe dementia. However, they found decision‐making processes and communication about nutrition and hydration were emotionally demanding and poorly supported in acute hospitals. The co‐design groups developed the aims of the decision guide to support conversations and shared decision‐making processes in acute hospitals, and help people reach evidence‐based decisions. It was designed to clarify decision‐making stages, provide information and elicit the values/preferences of everyone involved. It encouraged person‐centred care, best‐interests decision‐making and multidisciplinary team working. From user testing, family carers and hospital professionals thought the decision guide could help initiate conversations and inform decisions. The final decision guide was disseminated and is being used in clinical practice in England. Conclusion We used rigorous and transparent processes to co‐design the decision guide with everyone involved. The decision guide may facilitate conversations about nutrition and hydration and help people reach shared decisions that meet the needs and preferences of people with severe dementia. Future evaluation is required to test its real‐world impacts. Patient or Public Contribution People with mild dementia, family carers and hospital professionals contributed to the design of the decision guide through the interviews and co‐design workshops. PPI members helped design study procedures and materials and prepare this manuscript.